Chilling without regrets: Deciphering the effects of cryopreservation on the epigenetic properties of frozen cells will benefit the applications of cryo‐technology. (11th February 2016) - Chatterjee, Anamika; Saha, Debapriya; Glasmacher, Birgit; Hofmann, Nicola
Abstract : Cryopreservation is used widely in medicine and research to store cells and tissues. Surprisingly, the nature and impact of epigenetic changes that result from freezing is not well studied. Research into these changes is urgent to improve the safety and efficacy of cryopreservation for medical applications.